Conducting Court Proceedings in Contested Divorce Cases for Persons with Disabilities at Class 1a Malang Religious Court - Kilihu, Lia Rosa Fauziah; Muhibbin, Moh.; Suratman, Suratman; Ilmania, Nurika Falah (JUSTISI, 2024)
People with disabilities often receive unequal treatment, especially in the justice process. People with disabilities have equal rights in everything, including the legal process. However, there are barriers for persons with disabilities in the Religious Court of Malang. The purpose of this writing is to find out the obstacles and efforts that occur to persons with disabilities during the legal process.  The research method used is empirical juridical, by conducting interviews or observations at the Malang Class 1A Religious Court.  In this study, it was found that the barriers to lawyering in the Malang Religious Court were insufficient facilities for persons with disabilities, such as the use of language in communication for persons with disabilities. The purpose of legal services for persons with disabilities when dealing with the law in the Religious Courts is to realize inclusive religious justice services. The obstacles in Religious Court of Malang continue to be pursued optimally and gradually by the Malang Religious Court through capacity building for human resources to understand disabilities within the scope of the court which is needed as part of excellent service, which aims to provide information and information to parties with disabilities without hesitation.